ECOPRINT COLOR FASTNESS RESISTANCE ON GOATSKIN MEDIA AGAINST WET RUB AND SUNLIGHT - Aini, Nurul; Prahastuti, Endang; Fatkhi Rohmah, Mayang (E-Journal of Cultural Studies; Vol 15 No 2 (2022): Volume 15, Number 2, May 2022, 2022)
Many artisans prefer to use artificial (synthetic) dyes because they are faster and easier. However, chemical substances from synthetic dye waste are harmful to the environment. Eco-print technique minimizes environmental losses due to natural  coloring techniques on printing or transferring colors and motifs from plants directly to the medium. This study aimed to determine the color fastness of eco-print on goatskin material against wet rubbing and sunlight using mordant and tunjung . This  research was descriptive research with a quantitative approach. The results showed that  the average evaluation value of color fastness to sunlight was 4.75, better than wet   rubbing, which got an average evaluation value of 4.42. The bivariate analysis showed the value of sig. (0.043) or H0 was rejected. In conclusion, there was a difference in  color fastness from eco-print on goatskin material against wet rubbing and sunlight. Keywords: eco-print, fastness resistance, goatskin.